2013
DOI: 10.1093/mnras/stt1843
|View full text |Cite
|
Sign up to set email alerts
|

Radiation pressure confinement – I. Ionized gas in the ISM of AGN hosts

Abstract: We analyze the hydrostatic effect of AGN radiation pressure on optically thick gas in the host galaxy. We show that in luminous AGN, the radiation pressure likely confines the ionized layer of the illuminated gas. Radiation pressure confinement (RPC) has two main implications. First, the gas density near the ionization front is 7 × 10 4 L i,45 r −2 50 cm −3 , where L i,45 is the ionizing luminosity in units of 10 45 erg s −1 and r 50 is the distance of the gas from the nucleus in units of 50 pc. Second, as sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 112 publications
8
83
0
Order By: Relevance
“…Following eqn. (10) in Stern et al 2014, using R = 275 kpc, the average ionizing photon flux for our sample Q ion ≡ 4πR 2 Φ LL ≈ 10 57 s −1 , L i,45 = Q ion h/ν = 6 × 10 46 erg s −1 , and τ dust = 0.05, we obtain n H = 0.7 × 10 −2 cm −3 , remarkably close to what we found. However, to establish a RPC scenario on such large scales one would need a particular tuning of the time scales as the photons need to reach 300 kpc from the source.…”
Section: Comparison With Previous Deep Observationssupporting
confidence: 87%
See 1 more Smart Citation
“…Following eqn. (10) in Stern et al 2014, using R = 275 kpc, the average ionizing photon flux for our sample Q ion ≡ 4πR 2 Φ LL ≈ 10 57 s −1 , L i,45 = Q ion h/ν = 6 × 10 46 erg s −1 , and τ dust = 0.05, we obtain n H = 0.7 × 10 −2 cm −3 , remarkably close to what we found. However, to establish a RPC scenario on such large scales one would need a particular tuning of the time scales as the photons need to reach 300 kpc from the source.…”
Section: Comparison With Previous Deep Observationssupporting
confidence: 87%
“…28 Intriguingly this value is in agreement with a radiation pressure confinement scenario (RPC; Stern et al 2014), shown to be in place at least up to 10 kpc from an AGN. In this scenario the radiation pressure is the main contributor to the gas pressure so that P rad ∼ Pgas, and the density profile is then shown to follow a simple relation.…”
Section: Comparison With Previous Deep Observationssupporting
confidence: 66%
“…This is not unexpected, since the Balmer photons are likely extincted by dust within the NLR clouds, thus increasing (Hα/Hβ) int above the Case B value (see fig. 6 in Stern, Laor, & Baskin 2014, and also Dopita et al 2002). The observed slope of the relation between (Hα/Hβ) obs and α opt in the NLR is shallower than the expected slope derived in eqn.…”
Section: Hα/hβ Vs α Optmentioning
confidence: 54%
“…We include in the calculation the effect of radiation pressure on the dust grains, which is significant at U 0.01 (Dopita et al 2002;Groves, Dopita, & Sutherland 2004;Stern et al 2014). We use the depleted ISM abundance set implemented in cloudy, except for the sodium abundance which we assume has solar abundance.…”
Section: The Expected Ew(naid)mentioning
confidence: 99%
“…RPC conditions have been shown to apply in at least some star forming regions (Draine 2011;Yeh & Matzner 2012;Yeh et al 2013;Verdolini et al 2013), in AGN emission line regions (Dopita et al 2002;Baskin et al 2014a;Stern et al 2014aStern et al , 2016, in AGN absorption line regions Baskin et al 2014b), and possibly in the CGM of quasar hosts, in the part exposed to the quasar radiation (Arrigoni Battaia et al 2016). Assuming that dust grains are embedded in the CGM gas, as suggested by the results of Ménard et al (2010), then the dominant contribution to the integral in eqn.…”
Section: Radiation Pressure Confinementmentioning
confidence: 99%